Utilization of CORDEX-SEA Rainfall Data for Rainfall Projections Using the RCP 4.5 Secenario in the Beringin Sila Dam Catchment Area Sumbawa Regency - Iwin Satria; Sumiadi; Sri Wahyuni (Jurnal Penelitian Pendidikan IPA, 2025)
Climate change poses significant challenges to water resource management, particularly in regions dependent on reservoirs. This study evaluates the performance of CORDEX-SEA rainfall data in the Beringin Sila watershed and applies a bias correction using the Linear Scaling (LS) method. Historical analysis for 2001–2022 revealed that the raw CORDEX-SEA output overestimated rainfall, with a mean of 147.88 mm/month compared to 93.10 mm/month observed (PBIAS = 35.5%, Willmott’s d = 0.03). After applying LS, model accuracy improved substantially, yielding an adjusted mean of 100.30 mm/month, PBIAS of 3.07%, Willmott’s d of 0.748, and correlation coefficient of 0.580. These results confirm that LS effectively reduces systematic bias. The corrected dataset was then used to project rainfall for 2023–2050 under the RCP 4.5 scenario. Projections indicate an average of 98.49 mm/month, or 5.8% higher than the historical baseline, with considerable interannual variability ranging from less than 50 mm in dry years to more than 300 mm in wet years. Such findings highlight both the potential for modestly increased water availability and the need for adaptive reservoir operation to manage variability across wet and dry seasons. The results provide a valuable reference for future water balance studies and operational strategies in newly constructed reservoirs such as Beringin Sila.